Cecal volvulus complicated by evisceration case report. Issue 1 (18th January 2021) - Johnson, Kylie; Williams, Ben; Steen, Eric
Abstract: This case of bowel obstruction with multiple postoperative complications provides unique insight into the challenges faced by providers caring for intellectually disabled patients with acute surgical abdominal pathology and poor compliance. In this case, the component separation was utilized as a method of facilitated wound closure and compliance in a postoperative course highlighted by both dehiscence and wound infection. The patient, only able to communicate the presence of abdominal pain due to his disability, was surgically managed for a bowel obstruction secondary to a cecal volvulus. The difficulty in initial communication and patient noncompliance help illustrate the individualized care these patients require. This report will demonstrate both the challenges present in the management of intellectually disabled patients with abdominal wounds, as well as the use of component separation in providing both initial wound closure and continued wound integrity with the goal of reducing postoperative complications in patients with decreased compliance.